Analysis of Internal Control System of Merchandise Inventory at Mulia Mart Retail Stores - Muhammad Saddam; Rigamala Basyir; Nardi Gunawan (Peneliti.net, 2023)
This study aims to find out how the systems and procedures for inventory of merchandise applied to Mulia Mart are in accordance with the objectives of internal control. To obtain the data used in compiling this research, the authors needed data collection tools in the form of interviews, observational observations and documentation. The method used is descriptive qualitative method. The results of this study can be concluded that the internal control system for merchandise inventory at the Mulia Mart retail store is in accordance with the objectives of internal control for merchandise inventory, the merchandise has been running effectively, it only remains to improve the implementation system so that it is even better in the future